Effects of chemical fertilizer combined with organic manure on Fuji apple quality, yield and soil fertility in apple orchard on the Loess Plateau of China - Zuoping, Zhao; Sha, Yan; Fen, Liu; Puhui, Ji; Xiaoying, Wang; Yan'an, Tong (International Journal of Agricultural and Biological Engineering, 2014)
To evaluate the effects of chemical fertilizer combined with organic manure on apple yield, quality and soil fertility, an experiment was conducted in an apple orchard on the Loess Plateau of China. Six treatments, i.e., 1) no nitrogen (N) with chemical phosphorus (P) and potassium (K) (PK), 2) no P with chemical N and K (NK), 3) no K with chemical N and P (NP), 4) N, P and K chemical fertilizers only (NPK), 5) swine manure (M) only (M), and 6) half chemical fertilizers combined with half swine manure (NPKM) were included with three replications for each. The NPKM treatment achieved 36.9 t/ha average annual yield, which was 42.5% greater than the yield of PK treatment. The average annual yields followed the sequence of NPKM>NPK>M>NK>NP>PK. In NPKM treatment 71.3% of the collected apples had an apple diameter greater than 80 mm compared with 58.2%, 41.5 % and 37.2% in NK, PK and NP treatments, respectively. The sugar to acid (S:A) ratio was the greatest in NPKM treatment. The results of Vitamin C, soluble solid and firmness showed that NPKM treatment had the highest values. The concentration of soil organic carbon (SOC) in the 0 to 20 cm depth of soil was significantly affected by addition of M. Compared to the antecedent soil properties, the SOCS in the NPKM and M treatments were increased by 28.8%, 29.4%, and TN contents were 56.5, 49.8% more for soil at 0–20 cm depths, respectively. The major soil nutrients of N, P and K were also significantly increased by M and NPKM treatments in surface soil for five years. The data support the conclusion that, for a production of 35-40 t/ha in an apple orchard on the Loess Plateau of China, the 25-30 t/ha organic manure, 160-200 kg/ha N, 100-150 kg/ha P2O5 and 120-160 kg/ha K2O were the most suitable fertilizer application. The finding will be helpful for harmonious development of apple production technology, economic income increase for farmers, and improvement of the apple orchard ecosystem.Keywords: organic manure, mineral fertilizer, apple yield, quality, soil fertilityDOI: 10.3965/j.ijabe.20140702.006Citation: Zhao Z P, Yan S, Liu F, Ji P H, Wang X Y, Tong Y A. Effects of chemical fertilizer combined with organic manure on Fuji apple quality, yield and soil fertility in apple orchard on the Loess Plateau of China. Int J Agric & Biol Eng, 2014; 7(2): 45－55.